Mechanical behaviour of polyvinyl alcohol-engineered cementitious composites (PVA-ECC) tunnel linings subjected to vertical load. (January 2020) - Ding, Zude; Wen, Jincheng; Li, Xiaoqin; Fu, Jiang; Ji, Xiafei
Highlights: Mechanical behaviour of ECC and R/ECC linings were investigated. ECC and R/ECC linings exhibited multiple crack distributions. ECC improved ductility and toughness of lining. ECC lining performed with better toughness when the soil stiffness was smaller. R/ECC linings exhibited better deformation capability compared with RC and ECC linings. Abstract: Polyvinyl alcohol-engineered cementitious composites (PVA-ECC) have been attracted considerable attention due to the high toughness, excellent crack resistance, remarkable strain hardening and good durability. However, PVA-ECC application in tunnel lining is far from advanced. To evaluate the adaptability of PVA-ECC lining in mountain tunnels, a series of 1/5-scale tunnel lining specimens were tested to investigate the mechanical behaviour of traditional reinforced concrete (RC), PVA-ECC and steel-reinforced ECC (R/ECC) linings under vertical loading. The influence of subgrade stiffness on the mechanical behaviour of ECC linings was analysed. Experimental results showed that the ECC and R/ECC lining specimens exhibited multiple crack distributions and excellent cracking control capability, which showed better ductility and toughness compared to the traditional RC lining specimen. The PVA-ECC and R/ECC linings are flexible supports with initial stiffness values less than that of the traditional RC lining. Smaller subgrade stiffness may induce lager tensile stress distribution range of the linings, where the toughness of ECC could be fully utilized.